A Randomized Controlled Pilot Study Evaluating the Safety and Efficacy of Nifuroxazide in Patients with Ulcerative Colitis - AlRasheed HA; Abdallah MS; El-Khateeb E; Kamal M; Alrubia S; Alsegiani AS; Ahmed TI; Bahaa MM (Drug Design, Development and Therapy)
Hayam Ali AlRasheed,1 Mahmoud S Abdallah,2,3 Eman El-Khateeb,4,5 Marwa Kamal,6 Sarah Alrubia,7 Amsha S Alsegiani,7 Tarek I Ahmed,8 Mostafa M Bahaa9 1Department of Pharmacy Practice, College of Pharmacy, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 2Department of Clinical Pharmacy, Faculty of Pharmacy, University of Sadat City (USC), Sadat City, Menoufia, 32879, Egypt; 3Department of PharmD, Faculty of Pharmacy, Jadara University, Irbid, 21110, Jordan; 4Clinical Pharmacy Department, Faculty of Pharmacy, Tanta University, Tanta, Egypt; 5Certara Predictive Technologies (CPT), Simcyp Division, Sheffield, UK; 6Clinical Pharmacy Department, Faculty of Pharmacy, Fayoum University, Fayoum, Egypt; 7Pharmaceutical Chemistry Department, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 8Internal Medicine Department, Faculty of Medicine, Fayoum University, Fayoum, Egypt; 9Pharmacy Practice Department, Faculty of Pharmacy, Horus University, New Damietta, EgyptCorrespondence: Mostafa M Bahaa, Pharmacy Practice Department, Faculty of Pharmacy, Horus University, New Damietta, Egypt, Tel +201025538337, Email mostafabahaamnf@gmail.com; mbahaa@horus.edu.egBackground: The therapeutic potential of nifuroxazide in colitis has been explored in several experimental studies of ulcerative colitis (UC).Aim: To evaluate the efficacy of nifuroxazide in patients with UC.Methods: Fifty patients with mild to moderate UC were randomly assigned into two groups (n = 25 each). The placebo group received a placebo alongside mesalamine (1 g three times daily [t.i.d.]) for six months. The nifuroxazide group received nifuroxazide (200 mg twice daily) in combination with mesalamine (1 g t.i.d). A gastroenterologist assessed disease severity using the partial Mayo score (PMS). Serum levels of C-reactive protein (CRP), nuclear factor kappa B (NF-κB), interleukin-6 (IL-6), and signal transducer and activator of transcription 3 (STAT3) were measured before and after treatment. Quality of life was evaluated using the Inflammatory Bowel Disease Questionnaire (IBDQ-32). Primary outcomes: Change in PMS. Secondary outcomes: change in IBDQ-32 and in the level of measured biomarkers.Results: Baseline measurements were comparable between groups (p > 0.05). Post-treatment values showed significant improvements within both groups compared to baseline. However, the nifuroxazide group demonstrated significantly greater improvements than the placebo group, including reductions in PMS (p = 0.005) and increases in IBDQ scores (p = 0.002). Additionally, significant decreases were observed in IL-6 (p = 0.03), NF-κB (p = 0.03), CRP (p = 0.02), and STAT3 (p = 0.03) levels. The placebo group had a response rate of 56% (14/25) and a remission rate of 24% (6/25), whereas the nifuroxazide group achieved a response rate of 76% (19/25) and a remission rate of 56% (14/25), based on PMS.Conclusion: Co-administration of nifuroxazide with mesalamine improved clinical outcomes, including higher response and remission rates, reduced inflammation by reducing IL-6/STAT3, and enhanced quality of life in patients with UC, compared to mesalamine alone.Trial Registration Identifier: NCT05988528.Keywords: nifuroxazide, IL-6, STAT3, PMS, ulcerative colitis